The impact of simultaneous batch turn downs and targeted kidney utilization decisions on patient survival - Diwakar Gupta; Jingyao Huang; Paola Martin (PLoS ONE, 2026)
In the US, Organ Procurement Organizations (OPOs) procure deceased-donor kidneys, whereas Transplant Programs (TxPs) make utilization decisions for candidates listed at their centers. For each donor, candidates are ranked in a strict priority sequence determined by the national allocation rules. Higher-ranked candidates have the right of first refusal over lower-ranked candidates. TxPs are expected to utilize kidneys based on the merits of performing a transplant for each candidate independently of other candidates. However, they frequently utilize kidneys for lower-ranked candidates. This phenomenon is called list diving. The prevalence of list diving has been documented in the literature but its impact on post-transplant outcomes has not been studied. Moreover, all of the reasons why TxPs exercise list diving are not observed in archival data. Therefore, we examine whether utilization decisions that occur either before or concurrently with multiple declines (referred to as batch turn downs) of higher-ranked candidates result in higher recipient and graft survival after accounting for treatment endogeneity. The out-of-sequence transplants identified via the time-based criterion are referred to as targeted placements (TPs). Such transplants signal TxPs’ exercise of clinical judgment. We find that TPs reduce the waiting time for recipients (average time to transplant: 2.20 years for TP recipients vs. 2.64 years for non-targeted recipients, p –value < 0.01) while lengthening it for skipped candidates (average wait time until the first offer: 1.64 years for skipped candidates vs. 1.37 years for non-skipped candidates, p –value < 0.01). However, TPs do not significantly improve the survival chances of recipients in aggregate, despite the shortened waiting time. Concurrently, TPs prolong skipped candidates’ waiting time and the extra wait does not improve survival chances of those among them who eventually receive transplants.